Development of best practices for more holistic assessments of carrying capacity of aquaculture. (1st June 2021) - Weitzman, Jenny; Filgueira, Ramón; Grant, Jon
Abstract: Carrying Capacity (CC) has emerged as a potential tool to sustainably manage human activities such as aquaculture. However, interdisciplinary and integrated frameworks for holistic CC assessments are still missing. The goal of this study was to generate expert consensus on best evaluative practices for holistic CC assessments of ocean-based salmon aquaculture. To achieve this goal, a 3-round Delphi study was conducted with 21 aquaculture and carrying capacity experts from around the world. Experts emphasized that the holistic CC process should i) engage all stakeholders in the process, ii) consider the combination of social, political, ecological, and economic aspects, iii) respond to changes over time, iv) consider multiple spatial and temporal scales, and v) be understandable and clear to all stakeholders involved. Furthermore, the expert panel emphasized the need for a cyclical and dynamic process that allows for the incorporation of feedback in the planning stages, embracing adaptive management. Due to the early stages of truly holistic assessments, the experts recognized challenges related to knowledge uncertainties and lack of approaches to integrate socio-economic data with ecological and physical data, potential conflicts arising from a multi-stakeholder process, and ill-equipped governance structures. The proposed guidelines and framework could help address some of the conceptual and procedural barriers to implementing holistic assessments into decision-making and may position CC as a useful decision-support tool for governments seeking sustainable aquaculture management. Highlights: Delphi method generated a framework for holistic aquaculture carrying capacity (CC). Best practices for CC definitions, scales, stakeholders and evaluation tools and methods. An adaptive step-wise process can facilitate the implementation of CC best practices. Holistic CC assessments help visualize risks and inform marine spatial planning. Implementation will face external knowledge, institutional and attitudinal barriers.